The Influence of Customer Reviews, Working Hours, and Competition on The Number of Orders for Grabbike Drivers (Case Study on Grabbike Drivers in Malang City) - Maria Embun Intanin Jelita; Muhamad Rifa'i; Noviana Yaniar Suprajitno (IRDH International Journal of Social Sciences & Humanities, 2026)
This study aims to examine the effects of customer reviews, working hours, and competition on the number of orders received by GrabBike drivers, both partially and simultaneously. The study employs a quantitative approach using survey data collected from 50 GrabBike drivers in Malang City through a Likert-scale questionnaire (1–5). Data analysis is conducted using multiple regression analysis, including t-tests, F-tests, and the coefficient of determination (R²). The results indicate that customer reviews have a negative and significant effect on the number of orders, while working hours have a positive and significant effect. Competition shows a positive but not significant effect on the number of orders. Simultaneously, customer reviews, working hours, and competition have a positive and significant effect on the number of orders, with a coefficient of determination of 28.1%. These findings suggest that working hours play a crucial role in increasing order volume, while the role of competition remains less influential.